Integrated Tourism Development Strategy Model in Increasing PAD and Community Economy in Southeast Sulawesi Province - Muh. Nur; Sahbin Barqi; Andi M. Budihard; Asraf Asraf; Kusman Paluala (AIBPM Publisher, 2025)
This study was conducted with the objectives of: (1) identifying factors that influence the development of integrated tourism (2) obtaining information on tourism destination management models to achieve tourism development that can increase Regional Income (PAD) and the community economy, and (3) obtaining information on strategies and concepts. The research locations were Bau-Bau City, North Konawe, Bombana, and Kolaka Regency. The analysis methods used were Partial Least Square (PLS) analysis and SWOT analysis. The conclusion of the results of this study shows are as follows: (1) Facilities and infrastructure in tourist areas currently only consist of several types. The existing facilities and infrastructure do not meet tourism quality standards due to lack of attention from the local government; (2) The Tourism Office faces several challenges in developing the tourism sector. This is because tourism is not considered a primary or leading sector in these areas; (3) The development of the tourism sector cannot be separated from the progress of information technology which is increasingly spreading in various regions in Southeast Sulawesi Province. The suggestion from the results of this study is that the Southeast Sulawesi government should hold/collect levies for each district that has tourist attractions to increase PAD.